233k views
5 votes
Please solve these two questions

Please solve these two questions-example-1

1 Answer

2 votes

Answer:

Question 4

Simplifying the expression
(x^2-10x-24)/(x^2-3x-108) we get
(x-2)/(x-9) and x≠9 or x≠2

Option D is correct option.

Question 5

Simplifying the expression:
(8x-16)/(x^2-13x+22) we get
(8)/(x-11), x\\eq 11

Option C is correct.

Explanation:

Question 4

Simplify completely
(x^2-10x-24)/(x^2-3x-108)

For simplifying the above expression we have to find find factors of numerators and denominators

First finding factors of numerator
x^2-10x-24


x^2-10x-24\\ = x^2-12x+2x-24 \\= x(x-12)+2(x-12) \\=(x-12)(x-2)

So, the factors of
x^2-10x-24 are
(x-12)(x-2)

Now finding factors of denominator
x^2-3x-108


x^2-3x-108\\=x^2-12x+9x-108\\=x(x-12)+9(x-12)\\=(x+9)(x-12)

So, factors of
x^2-3x-108 are (x-12)(x+9)

Now, replacing numerators and denominators with their factors


(x^2-10x-24)/(x^2-3x-108)\\=((x-12)(x-2))/((x+9)(x-12))\\Cancelling\:(x-12) \: from\:numerator\:and\:denominator\\=(x-2)/(x-9)

so, simplifying the expression
(x^2-10x-24)/(x^2-3x-108) we get
(x-2)/(x-9) and x≠9 or x≠2

Option D is correct option.

Question No 5

Simplify the expression:
(8x-16)/(x^2-13x+22)

For simplifying the above expression we have to find find factors of numerators and denominators

First finding factors of numerator
8x-16

Taking 8 common:


8x-16\\=8(x-2)

So, factors of
8x-16 are
8(x-2)

Now finding factors of denominator :
x^2-13x+22


x^2-13x+22\\=x^2-11x-2x+22\\=x(x-11)-2(x-11)\\=(x-2)(x-11)

Now, replacing numerators and denominators with their factors


(8x-16)/(x^2-13x+22)\\=(8(x-2))/((x-11)(x-2))\\Cancelling\:(x-2)\\=(8)/(x-11), x\\eq 11

So, simplifying the expression:
(8x-16)/(x^2-13x+22) we get
(8)/(x-11), x\\eq 11

Option C is correct.

User Michael Waterfall
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.